TUGAS GEREJA SEBAGAI MISI KRISTUS DITINJAU DARI INJIL MATIUS 28:19-20 - Stafanus Sugiyanto (Jurnal Teologi Biblika, 2022)
The task of outreach or mission from the beginning had Christ commanded the disciples. When they were first called they were commanded in Matthew 28:19-20 "Go and make disciples of all nations." God does not want anyone to build His love to be bestowed on humans through the sacrifice of Jesus on the cross so that those who respond by believing in Him are eternal. This world is full of evil, many people who do not know the truth are under threat of eternal punishment. Who is responsible for breaking the news to them? It is none other than God's church/believers. Mission/apostello means to send with authority for a specific purpose to be accomplished. From the very beginning the church was founded/existed on a mission. In this paper, we will discuss "The Church's Duty as Christ's Mission Judging from the Gospel of Matthew 28:19-20." So it is clear that the task of confession/mission is the duty of the church, namely the duty of every believer. So the discussion includes the notion of the church and the notion of mission. Church / is a congregation / people who believe in Jesus as Lord and savior. Mission /apostello means to send with authority for a specific purpose to be accomplished.